Application of the Round Cross Game to Increase Active Participation of Students - Asih Banjarani, Wukir; Wijayanto, Benny; Candra Dinata, Vega (CV. Nusantara Sporta, 2024)
This study aims to enhance student participation in the learning process through the modification of the cross-round game. Increasing student engagement is crucial for supporting successful learning outcomes. The research was conducted on July 25, 2024, at SDN Babatan 1/456 Surabaya. Observations revealed that some students were not actively participating, feeling uninspired, and not bringing sports clothes, which affected their overall engagement in learning. This study employs the Classroom Action Research (CAR) method, where teachers or researchers identify classroom issues to improve teaching practices. Data were collected using a questionnaire. Analysis of the data indicates a notable improvement in student participation from Cycle 1 to Cycle 2. In Cycle 1, the average participation score was 50.78, which increased to 53.13 in Cycle 2. This represents a 5% increase in student participation due to the modified cross-round game at SDN Babatan 1/456 Surabaya. The findings demonstrate the effectiveness of the game modification in enhancing student engagement in the learning process.